Analisis Kesejahteraan Pegawai Berdasarkan Faktor Kepuasan Kerja, Komitmen Organisasi, dan Stres Kerja (Studi Pada Pegawai Dinas Syariat Islam Kabupaten Bireuen) - Fatimah Fatimah; Raihan Iskandar; Luthfi Luthfi; Musrizal Musrizal (Aceh Cooperative Care, 2026)
This article presents and analyzes employee well-being based on factors such as job satisfaction, organizational commitment, and job stress, conducted in a case study at the Islamic Sharia Office in Bireuen Regency. An associative method with a quantitative approach was applied using path analysis with total sampling. This study found: (1) a causal relationship exists between the variables of job satisfaction, organizational commitment, and job stress, with quite strong direct and indirect influences on employee well-being. (2) job satisfaction has a 23.47% effect, organizational commitment a 35.76% effect, and job stress a 34.54% effect on employee well-being. (3) The results of the correlation coefficient and determination (R-squared) analysis indicate that job satisfaction, organizational commitment, and job stress simultaneously influence employee well-being at the Islamic Sharia Office in Bireuen Regency by 40.1%.